2009
DOI: 10.1055/s-0030-1247776
|View full text |Cite
|
Sign up to set email alerts
|

Supracondylar Femoral Fracture After Anterior Cruciate Ligament Reconstruction with Transfemoral Fixation

Abstract: Femoral fractures following anterior cruciate ligament (ACL) reconstruction are rare. These injuries often are related to increased stresses at the femoral tunnel. Hamstring tendon autograft is often used for ACL reconstruction, and transfemoral fixation is one of many graft fixation techniques with few reported complications. This article reports an atraumatic transverse supracondylar femoral fracture occurring through the transfemoral fixation tract following hamstring ACL reconstruction in a 38-year-old wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Fracture patterns in these case studies ranged from intra-articular femoral condyle fractures to supracondylar fractures. Patients with supracondylar fractures tended to have extra-articular points of ACL ligament fixation, which was in keeping with the results of our case study [ 1 , 2 , 9 , 13 , 16 , 17 , 19 21 ]. Only one case study demonstrated fracture after remote ACL reconstruction 11 years postoperatively, while most studies reported fractures within 1 to 2 years of the initial operation [ 2 , 6 ].…”
Section: Discussionsupporting
confidence: 91%
“…Fracture patterns in these case studies ranged from intra-articular femoral condyle fractures to supracondylar fractures. Patients with supracondylar fractures tended to have extra-articular points of ACL ligament fixation, which was in keeping with the results of our case study [ 1 , 2 , 9 , 13 , 16 , 17 , 19 21 ]. Only one case study demonstrated fracture after remote ACL reconstruction 11 years postoperatively, while most studies reported fractures within 1 to 2 years of the initial operation [ 2 , 6 ].…”
Section: Discussionsupporting
confidence: 91%
“…Both devices require their own respective insertion techniques and apart from missing the femoral tunnel altogether during graft placement which can occur with both devices, other devicespecific complications have occurred with the Transfix device during insertion such as broken or twisted graft-passing wires [12][13][14] . Supracondylar femur fractures have been described with the use of Transfix too though this was not encountered in our study 15,16 . We had one patient which had a broken Transfix pin which presented as subcutaneous swelling necessitating surgical removal.…”
Section: Discussionmentioning
confidence: 52%
“…Supracondylar femoral fractures (with or without intraarticular extension) have been reported after bone-patellar tendon-bone reconstruction, 9,12 through the femoral screw hole after reconstruction with a ligament augmentation device, 4 through the site of transfemoral fixation in an autologous hamstring graft procedure, 6 and in association with a prosthetic graft. 10 Isolated condylar fractures are rarer still; however, they have been reported propagating through the site of staple fixation on the lateral femoral cortex in conjunction with a hamstring graft 7 after overdrilling and cortical perforation in the case of a bone-patellar tendonbone reconstruction, 5 and as late as 11 yr postoperatively when a fracture propagated through the accessory femoral tunnel from a cross-pinning ligament fixation device.…”
Section: Discussionmentioning
confidence: 99%